Copper deposition on fabrics by rf plasma sputtering for medical applications - Segura, G.; Guzmán, P.; Zúñiga, P.; Chaves, S.; Barrantes, Y.; Navarro, G.; Asenjo, J.; Guadamuz, S.; Vargas, V.; Chaves, J. (Institute of Physics Publishing, 2015)
The present work is about preparation and characterization of RF sputtered Cu films on cotton by the usage of a Magnetron Sputter Source and 99.995% purity Cu target at room temperature. Cotton fabric samples of 1, 2 and 4 min of sputtering time at discharge pressure of 1×10-2 Torr and distance between target and sample of 8 cm were used. The main goal was to qualitatively test the antimicrobial action of copper on fabrics. For that purpose, a reference strain of Escherichia Coli ATCC 35218 that were grown in TSA plates was implemented. Results indicated a decrease in the growth of bacteria by contact with Cu; for fabric samples with longer sputtering presented lower development of E. coli colonies. The scope of this research focused on using these new textiles in health field, for example socks can be made with this textile for the treatment of athlete's foot and the use in pajamas, sheets, pillow covers and robes in hospital setting for reducing the spread of microorganisms. © Published under licence by IOP Publishing Ltd.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84938151607&partnerID=40&md5=bf2da795caced442546f442aa330773a
Keywords: Algodón; Microorganismos; Cobre; Temperatura; Research Subject Categories::TECHNOLOGY::Engineering physics::Plasma physics with fusion; Bacterias